A method for preparing sodium lignin sulfonate modified attapulgite chitosan proton exchange membrane
Through the combination of sodium lignin sulfonate modified concave and convex rod soil and chitosan, the problems of attenuation and poor mechanical properties of the proton exchange membrane at high temperatures are solved, and the mechanical properties and proton conductivity of the proton exchange membrane are improved. Suitable for high temperature operation of fuel cells and direct methanol fuel cells.
Patent Information
- Application Number
- CN202211007519.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-22
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2042-08-22
AI Technical Summary
The perfluorosulfonic acid proton exchange membrane in existing proton exchange membrane fuel cells has attenuated performance at high temperatures, poor mechanical properties, and is not suitable for direct methanol fuel cells. New proton exchange membrane materials are needed.
Sodium lignin sulfonate modified concave and convex rod soil is combined with chitosan, and dopamine coats concave and convex rod soil and physically mixes it with sodium lignin sulfonate to form a composite material, improving its mechanical properties and protons in the proton exchange membrane Conductivity.
It significantly improves the mechanical properties and proton conductivity of the proton exchange membrane, solves the problems of poor dispersion of concave and convex rod soil and lacks proton transmission channels, and is suitable for high-temperature operation of fuel cells and direct methanol fuel cells.
Smart Images

Figure BDA0003809582290000071 
Figure BDA0003809582290000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fuel cells, and in particular to a method for preparing a sodium lignin sulfonate modified attapulgite chitosan proton exchange membrane. Background Art
[0002] Proton Exchange Membrane Fuel Cells (PEMFC) have the advantages of fast startup speed, high specific power and specific energy, and are ideal power sources for decentralized power stations, mobile power sources, electric vehicles and other equipment. As a core component of proton exchange membrane fuel cells, proton exchange membranes (PEMs) not only act as diaphragms to separate the positive and negative poles of the battery, but also play a role in transferring protons and blocking electrons in the battery. Its performance directly determines the performance of the battery. In order to meet the application requirements of PEMFC, PEMs must have good thermal and chemical stability, fuel barrier properties, mechanical properties, and excellent proton conductivity (proton conductivity>0.01S cm -1 ). At present, the commercialized proton exchange membrane is mainly perfluorosulfonic acid proton exchange membrane (PFSA). Among them, the Nafion series membrane produced by DuPont in the United States has the largest market share. The perfluorosulfonic acid proton exchange membrane has excellent mechanical properties, thermal and chemical stability, and strong proton conductivity. However, there are also some shortcomings, such as complex preparation process, harsh preparation conditions and high price; secondly, due to its low glass transition temperature, the proton conductivity, chemical and mechanical stability at high temperature (>100°C) will drop sharply, and the battery performance will be seriously attenuated. Moreover, the methanol permeability of the perfluorosulfonic acid proton exchange membrane is too large and is not suitable for direct methanol fuel cells. Therefore, it is very necessary to develop new proton exchange membrane materials.
[0003] Natural polymer materials are a hot topic in the energy field due to their abundant sources, low prices, and environmental friendliness. Chitosan (CS), as a natural polymer material, has been widely used in many fields such as biomedicine, food chemicals, water treatment, and membrane separation. In recent years, chitosan has also shown potential for application in the field of proton exchange membranes because of its low methanol permeability, easy film formation, and chemical modification. However, due to the poor mechanical properties of pure chitosan membranes and the -OH and -NH 2It is very easy to form intramolecular and intermolecular hydrogen bonds, resulting in a high proportion of rigid crystalline areas in the membrane, making it difficult for ions to migrate in the membrane, resulting in unsatisfactory conductivity. Therefore, how to effectively modify chitosan becomes the key. Among them, the organic-inorganic composite modification strategy is a hot topic in the current research field of proton exchange membrane modification. By adding various inorganic particles with different characteristics, the purpose of improving the characteristic performance of the composite membrane can be achieved.
[0004] Among the many inorganic fillers currently studied, attapulgite has its unique advantages. As a porous chain-layered magnesium-aluminum silicate mineral containing water, it has abundant reserves, low prices, large specific surface area and internal pore area, and has the characteristics of adsorption, catalysis, and enhancement. It is widely used in adsorption, catalysts, and reinforcements. Moreover, as a one-dimensional reinforcement, attapulgite has the advantages of high thermal stability and high strength, and is widely used in composite materials to improve mechanical strength and thermal stability. In recent years, due to its one-dimensional rod-like morphology, rich pore structure, easy chemical modification of the surface, high strength and thermal stability, and low price, attapulgite has quickly become an ideal filler for organic-inorganic composite modification of proton exchange membranes. The applicant's research group has conducted relevant research work in the early stage, using attapulgite or modified attapulgite as a filler and applying it to the composite modification research of proton exchange membranes, which can achieve the improvement of the comprehensive performance of composite membranes to a certain extent. However, due to the compatibility problem between attapulgite and organic polymer matrix, the dispersibility of attapulgite is irrational, and the improvement of conductivity performance by single attapulgite doping is limited. Lignin, as a natural polymer material, has been widely used as a dispersant to improve the dispersibility of various nanomaterials in recent years by preparing amphiphilic polymers from lignin. Lignin sulfonate (LS) is the product of lignin sulfonation. The sulfonic acid groups in the structure can be used as proton transfer sites, which can significantly improve proton conductivity. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a sodium lignin sulfonate modified attapulgite chitosan proton exchange membrane and explore its application potential in the field of chitosan proton exchange membrane modification. The proton exchange membrane prepared by the present invention has good mechanical properties and high proton conductivity.
[0006] The technical concept of the present invention is as follows: first, dopamine is used to coat the surface of attapulgite, then it is physically mixed with sodium lignin sulfonate to prepare a dopamine-coated attapulgite / sodium lignin sulfonate composite material, and finally it is doped with chitosan to prepare a proton exchange membrane.
[0007] The present invention provides a method for preparing a sodium lignin sulfonate modified attapulgite chitosan proton exchange membrane. First, dopamine is coated on the surface of attapulgite to introduce amino groups (-NH 2) and hydroxyl (-OH) active groups form a strong electrostatic interaction between attapulgite and sodium lignin sulfonate materials, which has a better composite material preparation effect compared with the simple physical mixing of attapulgite and sodium lignin sulfonate. Secondly, while sodium lignin sulfonate improves the dispersibility of attapulgite nanomaterials, its sulfonic acid groups provide proton sites for proton transfer, which can significantly improve the proton conductivity performance.
[0008] In order to achieve the above object, the present invention adopts the following technical scheme:
[0009] A method for preparing a sodium lignin sulfonate modified attapulgite chitosan proton exchange membrane, which specifically comprises the following steps:
[0010] (1) mixing attapulgite powder and dopamine, then adding tris(hydroxymethylaminomethane) hydrochloride solution thereto, dispersing them uniformly by ultrasonic treatment, and then stirring at room temperature for 20-24 hours. During the reaction, 0.1 mol / L hydrochloric acid solution is added dropwise to keep the pH of the reaction solution at 8-10. After the reaction is completed, the reaction solution is centrifuged, the solid is washed with anhydrous ethanol, and then dried at 80° C. for 24 hours to obtain dopamine-coated attapulgite;
[0011] The mass ratio of the attapulgite to dopamine is 1.0-1.5:1.0-1.5; the mass volume ratio of the attapulgite to tris(hydroxymethyl)aminomethane hydrochloride solution is 0.5-1.0:200, g / mL;
[0012] The particle size of the attapulgite is 200 mesh;
[0013] (2) The dopamine-coated attapulgite obtained in step (1) is mixed with sodium lignin sulfonate, and a small amount of deionized water is added thereto, and the mixture is ground for 2 to 3 hours. Deionized water is added to the ground product and ultrasonicated for 30 to 40 minutes, and stirred at room temperature for 1 to 2 hours; the reaction solution is filtered, washed with deionized water, and dried at room temperature for 48 hours to obtain sodium lignin sulfonate-modified dopamine-coated attapulgite;
[0014] The mass ratio of the dopamine-coated attapulgite to sodium lignin sulfonate is 1.0-1.5:2.0-3.0; before grinding, the mass ratio of the dopamine-coated attapulgite to the added deionized water is 1.0-1.5:0.5-1.0;
[0015] (3) adding the sodium lignin sulfonate modified dopamine coated attapulgite obtained in step (2) to a 2v / v% to 5v / v% acetic acid aqueous solution, and subjecting it to ultrasonic treatment to form a uniform dispersion, and adding chitosan to a 2v / v% to 5v / v% acetic acid aqueous solution to completely dissolve it, and then mixing the two solutions under stirring conditions, stirring at room temperature for 3 to 4 hours to make the mixture uniform, and subjecting it to ultrasonic degassing treatment for 20 to 30 minutes, pouring it onto a clean glass plate to form a film by casting, drying it at 80°C, and demolding it after cooling to room temperature; after taking it out, soaking it in 2M sulfuric acid for 24 hours, and then repeatedly washing it with deionized water, and finally drying it at room temperature to obtain a sodium lignin sulfonate modified dopamine coated attapulgite chitosan composite proton exchange membrane;
[0016] The mass percentage of the sodium lignin sulfonate modified dopamine coated attapulgite and chitosan is 2 / 100 to 10 / 100, preferably 4 / 100 to 8 / 100.
[0017] The technical solution of the present invention mainly solves the following problems:
[0018] 1. Dopamine-coated attapulgite was modified by sodium lignin sulfonate to solve the problem of poor dispersibility of attapulgite, give full play to its advantages as a material reinforcement, and improve the mechanical properties of the chitosan composite film.
[0019] 2. By utilizing the porous chain-layered structure characteristics of attapulgite, combined with the sulfonic acid groups contained in sodium lignin sulfonate and the strong electrostatic interaction between attapulgite and attapulgite, the problem of lack of ion transmission channels and proton action sites is solved, and the problem of unsatisfactory proton conduction performance of chitosan membrane is improved. DETAILED DESCRIPTION
[0020] The applicant will further explain the technical solution of the present invention in detail below in conjunction with specific embodiments, with the aim of enabling those skilled in the art to have a clearer understanding and recognition of the present application.
[0021] The following specific embodiments should not be understood or interpreted in any degree as limiting the scope of protection requested by the claims of this application.
[0022] The raw materials used in the following examples: dopamine, tris(hydroxymethyl)aminomethane hydrochloride, and anhydrous ethanol are all analytical grade (purchased from Sinopharm Group); the attapulgite is industrial grade with a particle size of 200 mesh (purchased from Jiangsu Huaiyuan Mining Company); the sodium lignin sulfonate is (purchased from Aladdin Chemical Reagent Co., Ltd.); the molecular weight of the chitosan is 1 million, and the degree of deacetylation is 92% (purchased from Zhejiang Jinke Biochemical Co., Ltd.); the 2v / v% acetic acid aqueous solution is prepared by laboratory-made pure water and analytical grade acetic acid, and the acetic acid is analytical grade (purchased from Sinopharm Group).
[0023] Example 1
[0024] A method for preparing a sodium lignin sulfonate modified attapulgite chitosan proton exchange membrane, comprising the following steps:
[0025] (1) In a dry and clean beaker, add 0.5g of attapulgite and 0.5g of dopamine, then add 200mL of tris(hydroxymethyl)aminomethane hydrochloride solution (1×TBE), disperse evenly by ultrasonic treatment, and then stir at room temperature for 24h. During the reaction, add an appropriate amount of 0.1mol / L hydrochloric acid solution to keep the pH of the reaction solution at 9-10. After the reaction solution is centrifuged, the solid is washed with anhydrous ethanol and then dried at 80°C for 24h to obtain dopamine-coated attapulgite.
[0026] (2) Weigh 0.5 g of the dopamine-coated attapulgite sample obtained in step (1), mix it with 1.0 g of sodium lignin sulfonate, add 0.5 mL of deionized water, grind for 2 h, add 30 mL of deionized water to the ground product, ultrasonicate for 30 min, and stir at room temperature for 2 h. Filter the reaction solution, wash the solid with deionized water, and dry it at room temperature for 48 h to obtain sodium lignin sulfonate-modified dopamine-coated attapulgite.
[0027] (3) Weigh 0.02g of the sodium lignin sulfonate modified dopamine coated attapulgite sample obtained in step (2), add 20mL 2v / v% acetic acid aqueous solution, and form a uniform dispersion by ultrasonic treatment. Add 1.0g chitosan to another beaker, dissolve it completely with 30mL 2v / v% acetic acid aqueous solution, and then mix the above two solutions under stirring conditions, stir at room temperature for 4h to make the mixture uniform, and after ultrasonic degassing for 30min, pour it on a clean glass plate for film casting, dry at 80℃, and demold after cooling to room temperature. After taking it out, soak it in 2M sulfuric acid for 24h, then repeatedly wash it with deionized water, and finally dry it at room temperature to obtain a sodium lignin sulfonate modified dopamine coated attapulgite chitosan composite proton exchange membrane.
[0028] The mass percentage of the sodium lignin sulfonate modified dopamine coated attapulgite to chitosan is 2 / 100.
[0029] Example 2
[0030] A method for preparing a sodium lignin sulfonate modified attapulgite chitosan proton exchange membrane, comprising the following steps:
[0031] (1) In a dry and clean beaker, add 0.5g of attapulgite and 0.5g of dopamine, then add 200mL of tris(hydroxymethyl)aminomethane hydrochloride solution (1×TBE), disperse evenly by ultrasonic treatment, and then stir at room temperature for 24h. During the reaction, add an appropriate amount of 0.1mol / L hydrochloric acid solution to keep the pH of the reaction solution at 9-10. After the reaction solution is centrifuged, the solid is washed with anhydrous ethanol and then dried at 80°C for 24h to obtain dopamine-coated attapulgite.
[0032] (2) Weigh 0.5 g of the dopamine-coated attapulgite sample obtained in step (1), mix it with 1.0 g of sodium lignin sulfonate, add 10 mL of deionized water, grind for 2 h, add 30 mL of deionized water to the ground product, ultrasonicate for 30 min, and stir at room temperature for 2 h. Filter the reaction solution, wash the solid with deionized water, and dry it at room temperature for 48 h to obtain sodium lignin sulfonate-modified dopamine-coated attapulgite.
[0033] (3) Weigh 0.04g of the sodium lignin sulfonate modified dopamine coated attapulgite sample obtained in step (2), add 20mL 2v / v% acetic acid aqueous solution, and form a uniform dispersion by ultrasonic treatment. Add 1.0g chitosan to another beaker, dissolve it completely with 30mL 2v / v% acetic acid aqueous solution, and then mix the above two solutions under stirring conditions, stir at room temperature for 4h to make the mixture uniform, and after ultrasonic degassing for 30min, pour it on a clean glass plate for casting film, dry at 80℃, and demold after cooling to room temperature. After taking it out, soak it in 2M sulfuric acid for 24h, then repeatedly wash it with deionized water, and finally dry it at room temperature to obtain a sodium lignin sulfonate modified dopamine coated attapulgite chitosan composite proton exchange membrane.
[0034] The mass percentage of the sodium lignin sulfonate modified dopamine coated attapulgite and chitosan is 4 / 100.
[0035] Example 3
[0036] A method for preparing a sodium lignin sulfonate modified attapulgite chitosan proton exchange membrane, comprising the following steps:
[0037] (1) In a dry and clean beaker, add 0.5g of attapulgite and 0.5g of dopamine, then add 200mL of tris(hydroxymethyl)aminomethane hydrochloride solution (1×TBE), disperse evenly by ultrasonic treatment, and then stir at room temperature for 24h. During the reaction, add an appropriate amount of 0.1mol / L hydrochloric acid solution to keep the pH of the reaction solution at 9-10. After the reaction solution is centrifuged, the solid is washed with anhydrous ethanol and then dried at 80°C for 24h to obtain dopamine-coated attapulgite.
[0038] (2) Weigh 0.5 g of the dopamine-coated attapulgite sample obtained in step (1), mix it with 1.0 g of sodium lignin sulfonate, add 10 mL of deionized water, grind for 2 h, add 30 mL of deionized water to the ground product, ultrasonicate for 30 min, and stir at room temperature for 2 h. Filter the reaction solution, wash the solid with deionized water, and dry it at room temperature for 48 h to obtain sodium lignin sulfonate-modified dopamine-coated attapulgite.
[0039] (3) Weigh 0.08g of the sodium lignin sulfonate modified dopamine coated attapulgite sample obtained in step (2), add 20mL of 2v / v% acetic acid aqueous solution, and form a uniform dispersion by ultrasonic treatment. Add 1.0g of chitosan to another beaker, dissolve it completely with 30mL of 2v / v% acetic acid aqueous solution, and then mix the above two solutions under stirring conditions, stir at room temperature for 4h to make the mixture uniform, and after ultrasonic degassing for 30min, pour it on a clean glass plate for film casting, dry it at 80℃, and demold it after cooling to room temperature. After taking it out, soak it in 2M sulfuric acid for 24h, then repeatedly wash it with deionized water, and finally dry it at room temperature to obtain a sodium lignin sulfonate modified dopamine coated attapulgite chitosan composite proton exchange membrane.
[0040] The mass percentage of the sodium lignin sulfonate modified dopamine coated attapulgite and chitosan is 8 / 100.
[0041] Example 4
[0042] A method for preparing a sodium lignin sulfonate modified attapulgite chitosan proton exchange membrane, comprising the following steps:
[0043] (1) In a dry and clean beaker, add 0.5g of attapulgite and 0.5g of dopamine, then add 200mL of tris(hydroxymethyl)aminomethane hydrochloride solution (1×TBE), disperse evenly by ultrasonic treatment, and then stir at room temperature for 24h. During the reaction, add an appropriate amount of 0.1mol / L hydrochloric acid solution to keep the pH of the reaction solution at 9-10. After the reaction solution is centrifuged, the solid is washed with anhydrous ethanol and then dried at 80°C for 24h to obtain dopamine-coated attapulgite.
[0044] (2) Weigh 0.5 g of the dopamine-coated attapulgite sample obtained in step (1), mix it with 1.0 g of sodium lignin sulfonate, add 10 mL of deionized water, grind for 2 h, add 30 mL of deionized water to the ground product, ultrasonicate for 30 min, and stir at room temperature for 2 h. Filter the reaction solution, wash the solid with deionized water, and dry it at room temperature for 48 h to obtain sodium lignin sulfonate-modified dopamine-coated attapulgite.
[0045] (3) Weigh 0.1g of the sodium lignin sulfonate modified dopamine coated attapulgite sample obtained in step (2), add 20mL of 2v / v% acetic acid aqueous solution, and form a uniform dispersion by ultrasonic treatment. Add 1.0g of chitosan to another beaker, dissolve it completely with 30mL of 2v / v% acetic acid aqueous solution, and then mix the above two solutions under stirring conditions, stir at room temperature for 4h to make the mixture uniform, and after ultrasonic degassing for 30min, pour it on a clean glass plate for film casting, dry at 80°C, and demold after cooling to room temperature. After taking it out, soak it in 2M sulfuric acid for 24h, then repeatedly wash it with deionized water, and finally dry it at room temperature to obtain a sodium lignin sulfonate modified dopamine coated attapulgite chitosan composite proton exchange membrane.
[0046] The mass percentage of the sodium lignin sulfonate modified dopamine coated attapulgite and chitosan is 10 / 100.
[0047] For comparison, 1.0 g of chitosan was completely dissolved in 30 mL of 2% acetic acid aqueous solution, poured onto a clean glass plate for film casting, dried at 80 ° C, and demolded after cooling to room temperature. After being taken out, it was soaked in 2M sulfuric acid for 24 hours, and then repeatedly washed with deionized water, and finally dried at room temperature to obtain a pure chitosan film.
[0048] Table 1 below lists the main performance index data of the sodium lignin sulfonate modified dopamine coated attapulgite chitosan composite proton exchange membrane and pure chitosan prepared in Examples 1 to 4. From the data in Table 1, it can be seen that the sodium lignin sulfonate modified dopamine coated attapulgite chitosan composite proton exchange membrane prepared by the present invention is expected to have broad application prospects in the field of fuel cells.
[0049] Table 1
[0050]
[0051] The film performance test conditions prepared in each embodiment are as follows:
[0052] (1) Proton conductivity: The resistance of the membrane was tested using the AC impedance method on a frequency response analyzer with a frequency sweep range of 1-10 7 Hz, the AC signal amplitude is 100mV, and the cut membrane (length × width = 3cm × 2cm) is tested by two-electrode AC impedance method. Before the test, the membrane sample is placed in deionized water at room temperature to reach saturation. The proton conductivity σ (S / cm) of the membrane is calculated by the following formula:
[0053]
[0054] Wherein, L and A are the distance between the two electrodes and the effective cross-sectional area of the membrane to be tested between the two electrodes, respectively, and R is the resistance of the membrane, which is calculated from the data obtained from the AC impedance test.
[0055] (2) Tensile strength and elongation at break: The film was cut into rectangular strips with a length of 40 mm and a width of 15 mm and tested on an electronic tensile testing machine at a tensile speed of 3 mm / min.
[0056] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principle of the present invention shall be regarded as equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a sodium lignin sulfonate modified attapulgite chitosan proton exchange membrane, characterized in that: The following steps are involved: (1) Surface coating of attapulgite by dopamine: attapulgite powder and dopamine were mixed, and then tris(hydroxymethyl)aminomethane hydrochloride) solution was added thereto, and the mixture was dispersed evenly by ultrasonic treatment, and then stirred at room temperature for 20-24 hours. During the reaction, 0.1 mol / L hydrochloric acid solution was added dropwise to maintain the pH of the reaction solution at 8-10. After the reaction was completed, the reaction solution was centrifuged, and the solid was washed with anhydrous ethanol and dried to obtain dopamine-coated attapulgite; (2) physically mixing the dopamine-coated attapulgite obtained in (1) with sodium lignin sulfonate to obtain sodium lignin sulfonate-modified dopamine-coated attapulgite; (3) The sodium lignin sulfonate modified dopamine coated attapulgite is mixed with a chitosan solution and cast into a film; the dry film is immersed in a sulfuric acid solution for cross-linking, and after washing and drying, a sodium lignin sulfonate modified attapulgite chitosan proton exchange membrane is obtained.
2. The preparation method according to claim 1, characterized in that: The specific steps include: (1) Mixing attapulgite powder and dopamine, then adding tris(hydroxymethyl)aminomethane hydrochloride solution thereto, dispersing them uniformly by ultrasonic treatment, and then stirring at room temperature for 20-24 hours. During the reaction, 0.1 mol / L hydrochloric acid solution is added dropwise to maintain the pH of the reaction solution at 8-10. After the reaction is completed, the reaction solution is centrifuged, and the solid is washed with anhydrous ethanol and dried to obtain dopamine-coated attapulgite; (2) The dopamine-coated attapulgite obtained in step (1) is mixed with sodium lignin sulfonate, and a small amount of deionized water is added thereto, and the mixture is ground for 2 to 3 hours. Deionized water is added to the ground product and ultrasonic treatment is performed for 30 to 40 minutes, and the mixture is stirred at room temperature for 1 to 2 hours. The reaction solution is filtered, washed with deionized water, and dried at room temperature to obtain sodium lignin sulfonate-modified dopamine-coated attapulgite. (3) The sodium lignin sulfonate modified dopamine coated attapulgite obtained in step (2) is added to a 2v / v% to 5v / v% acetic acid aqueous solution, and subjected to ultrasonic treatment to form a uniform dispersion. Chitosan is added to a 2v / v% to 5v / v% acetic acid aqueous solution to completely dissolve it. The two solutions are then mixed under stirring conditions and stirred at room temperature for 3 to 4 hours to make the mixture uniform. After ultrasonic degassing treatment, the film is cast; the dry film is immersed in a sulfuric acid solution for cross-linking, and washed with water and dried to obtain a sodium lignin sulfonate modified dopamine coated attapulgite chitosan composite proton exchange membrane.
3. The preparation method according to claim 2, characterized in that: In step (1), the mass ratio of attapulgite to dopamine is 1.0-1.5:1.0-1.
5.
4. The preparation method according to claim 2, characterized in that: In step (2), the mass ratio of the dopamine-coated attapulgite to sodium lignin sulfonate is 1.0-1.5:2.0-3.
0.
5. The preparation method according to claim 2, characterized in that: In step (3), the mass percentage of the sodium lignin sulfonate modified dopamine coated attapulgite and chitosan is 2 / 100 to 10 / 100.
6. The preparation method according to claim 2, characterized in that: In step (1), the mass volume ratio of the attapulgite to the tris(hydroxymethyl)aminomethane hydrochloride solution is 0.5-1.0:200, g / mL; In step (2), before grinding, the mass ratio of the dopamine-coated attapulgite to the added deionized water is 1.0-1.5:0.5-1.
0.
7. The preparation method according to claim 2, characterized in that: In step (3), the cross-linking step is: soak the dry film in 2 mol / L sulfuric acid for 24 hours.
8. Use of the sodium lignin sulfonate modified attapulgite chitosan proton exchange membrane prepared by the method according to any one of claims 1 to 7 in a fuel cell.
Citation Information
Patent Citations
Chitosan and quaternized attapulgite combined proton exchange membrane and preparation method thereof
CN109830727A
Chitosan and organic modified attapulgite immobilized with acid combined proton exchange membrane and preparation method thereof
CN109830728A